2015
DOI: 10.2147/ijn.s75398
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and mechanism of apoptosis induction by hypericin-mediated sonodynamic therapy in THP-1 macrophages

Abstract: Purpose To investigate the sonoactivity of hypericin (HY), together with its sonodynamic effect on THP-1 macrophages and the underlying mechanism. Materials and methods CCK-8 was used to examine cell viability. Confocal laser scanning microscopy was performed to assess the localization of HY in cells, reactive oxygen species (ROS) generation, and opening of the mitochondrial permeability transition pore (mPTP) after different treatments. Apoptosis was analyzed using Hoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 49 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…The rapidly expanding body of literature on SDT has shown that the development of sonosensitizers is one of the most essential factors in this treatment. In recent years, our group has identified sonosensitizers derived from extracts of Chinese herbs, including hypericin, curcumin, and hydroxyl acetylated curcumin [ 2 , 20 , 21 ]. However, further animal experiments and clinical translation of these sonosensitizers are limited by their lipophilic properties and rare application in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The rapidly expanding body of literature on SDT has shown that the development of sonosensitizers is one of the most essential factors in this treatment. In recent years, our group has identified sonosensitizers derived from extracts of Chinese herbs, including hypericin, curcumin, and hydroxyl acetylated curcumin [ 2 , 20 , 21 ]. However, further animal experiments and clinical translation of these sonosensitizers are limited by their lipophilic properties and rare application in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…At 30 min after HSYA-SDT, the cells were harvested by centrifugation and analyzed as previously described [ 20 ]. The images were observed and obtained with a transmission electron microscope (JEM-1220, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first evidence about SDT came from a study by Yumita et al in 1989, where various hematoporphyrin derivatives employed in PDT also caused a relevant cell damage after being exposed to US. 61 Since then, it has been shown that SDT can treat solid tumours, 62-65 leukaemia 66 and atherosclerosis 67 and, moreover, remove proliferative scars and kill pathogenic microorganisms. 68,69 Since SDT was developed on the basis of PDT, some suggest that SDT shares a similar therapeutic mechanism where the ultrasonic wave triggers the sonosensitizer inside the target tissue, with production of ROS that kill the target cells.…”
Section: Sonodynamic Therapymentioning
confidence: 99%